Unfinished exorcism: the legacy of apartheid in democratic Southern Africa - Carton, Benedict (Social justice, 2000)
Part of a special section on race, class, and state crime. In order to explore the origin of the current intolerance of many in Namibia and South Africa, the writer revisits the period immediately prior to Namibia's historic November 1989 election of its resistance movement, the Southwest African People's Organization, to form the new democratic government. He explains that many in Namibia and South Africa are afraid that AIDS and crime are beyond government control and are calling for a reintroduction of draconian measures. He argues that in the last days of apartheid, the specter of retribution may have provided scant opportunity for people to develop alternative strategies that could resolve major crises without resort to authoritarian methods. To give a picture of the situation, he presents vignettes from his election monitor's journal.